Seasonal activity patterns of reptiles in dry ecosystems (Zoological Records and Reviews, 2023)
Reptiles are ectothermic vertebrates whose activity patterns are fundamentally shaped by ambient thermal conditions,making them particularly sensitive to the extreme temperature ranges and seasonal precipitation patterns characteristicof dry ecosystems. The semi-arid and dry deciduous landscapes of the Deccan Plateau in peninsular India supportdiverse reptile communities whose seasonal activity patterns reflect both the annual temperature cycle and the highlyseasonal rainfall that drives prey availability and reproductive opportunities. This study presents a systematicassessment of seasonal activity patterns for 48 reptile species across 32 sites in the Deccan Plateau dry ecosystems ofAndhra Pradesh, Telangana, and Karnataka, using monthly standardised VES and camera trapping over two completeannual cycles (2021-2023). Activity season length, daily activity windows, seasonal body condition, and reproductivephenology are quantified for each species. Activity was highest during the monsoon and post-monsoon seasons for themajority of species (62.5%), driven by elevated prey availability and suitable thermal conditions. Geckos showedyear-round activity with nocturnal patterns; agamids were diurnal and showed strong seasonal compression in summer.Rock-dwelling species showed the least seasonal activity variation owing to thermal buffering by rocky substrates.Climate change implications for thermal activity windows and phenological mismatch are assessed using operativetemperature modelling.
Keywords: climate change vulnerability; agamids; geckos; semi-arid; VES; thermoregulation; Deccan Plateau; ectotherms; seasonal patterns; reptile activity